Performance of green waste biocovers for enhancing methane oxidation. (May 2015) - Mei, Changgen; Yazdani, Ramin; Han, Byunghyun; Mostafid, M. Erfan; Chanton, Jeff; VanderGheynst, Jean; Imhoff, Paul
Highlights: Green waste oxidized CH4 at high rates after relatively short periods of stabilization. A tracer gas plus carbon mass balance determined rates of CH4 oxidation. Significant CH4 generation occurred in relatively stable green waste. Models accounted for approximately 70% of seasonal variability in CH4 oxidation. Abstract: Green waste aged 2 and 24 months, labeled "fresh" and "aged" green waste, respectively, were placed in biocover test cells and evaluated for their ability to oxidize methane (CH4 ) under high landfill gas loading over a 15-month testing period. These materials are less costly to produce than green waste compost, yet satisfied recommended respiration requirements for landfill compost covers. In field tests employing a novel gas tracer to correct for leakage, both green wastes oxidized CH4 at high rates during the first few months of operation – 140 and 200 g/m 2 /day for aged and fresh green waste, respectively. Biocover performance degraded during the winter and spring, with significant CH4 generated from anaerobic regions in the 60–80 cm thick biocovers. Concurrently, CH4 oxidation rates decreased. Two previously developed empirical models for moisture and temperature dependency of CH4 oxidation in soils were used to test their applicability to green waste. Models accounted for 68% and 79% of the observed seasonal variations in CH4 oxidation rates for aged green waste. Neither model could describe similar seasonal changes for the less stable fresh green waste. This is the first field application and evaluation of these empirical models using media with high organic matter. Given the difficulty of preventing undesired CH4 generation, green waste may not be a viable biocover material for many climates and landfill conditions.